Methionine Sulfoxide Reductase B Regulates the Activity of Ascorbate Peroxidase of Banana Fruit - Lu Xiao; Guoxiang Jiang; Huiling Yan; Hongmei Lai; Xinguo Su; Yueming Jiang; Xuewu Duan (MDPI AG, 2021)
Ascorbate peroxidase (APX) is a key antioxidant enzyme that is involved in diverse developmental and physiological process and stress responses by scavenging H2O2 in plants. APX itself is also subjected to multiple posttranslational modifications (PTMs). However, redox-mediated PTM of APX in plants remains poorly understood. Here, we identified and confirmed that MaAPX1 interacts with methionine sulfoxide reductase B2 (MsrB2) in bananas. Ectopic overexpression of MaAPX1 delays the detached leaf senescence induced by darkness in Arabidopsis. Sulfoxidation of MaAPX1, i.e., methionine oxidation, leads to loss of the activity, which is repaired partially by MaMsrB2. Moreover, mimicking sulfoxidation by mutating Met36 to Gln also decreases its activity in vitro and in vivo, whereas substitution of Met36 with Val36 to mimic the blocking of sulfoxidation has little effect on APX activity. Spectral analysis showed that mimicking sulfoxidation of Met36 hinders the formation of compound I, the first intermediate between APX and H2O2. Our findings demonstrate that the redox state of methionine in MaAPX1 is critical to its activity, and MaMsrB2 can regulate the redox state and activity of MaAPX1. Our results revealed a novel post-translational redox modification of APX.